Analysis of a duopoly game with heterogeneous players participating in carbon emission trading - Zhao, Lingrui; Zhang, Jixiang (Nonlinear Analysis: Modelling and Control, 2014)
In this paper, a price competition model with two heterogeneous players participating in carbon emission trading is formulated. The stable conditions of the equilibrium points of this system are discussed. Numerical simulations are used to show bifurcation diagrams, strange attractors, and sensitive dependence on initial conditions. We observe that the speed of adjustment of bounded rational player may change the stability of the Nash equilibrium and cause the system to behave chaotically. In addition, we find that the price of emission permits plays an important role in the duopoly game. The chaotic behavior of the system has been stabilized on the Nash equilibrium point by applying delay feedback control method.
Keywords: carbon emission trading; price competition; heterogeneous players; Nash equilibrium; chaos